Bahan Baku Ketersediaan Pipa dalam Proses yang Mempengaruhi Hasil Produksi Pipa pada PT Jagor Jaya - Alif Nuron Al-Choiri; Daman Sudarman (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This research aims to determine the effect of the availability of raw materials and processes on production results at PT. production at PT Jagor Jaya. Data analysis shows that there is an influence on raw materials and processing on pipe production results. In this study the method method used is quantitative which is associative in nature. Use of data This quantitative data has 50 respondents, where the respondents are employees of the company. are employees of the company. In the data analysis carried out using SPSS, which serves to get the conclusion of the research conducted. research conducted. That it turns out that the availability of raw materials on production results gives a positive and significant influence which is indicated by the value tcount is greater than the ttable with a value of 5.265> 2.011, and the production process also has a positive and significant effect on production results, which is indicated by the value of tcount. production process also has a positive and significant effect on production results, which is indicated by the tcount value greater than greater than the t table with a value of 3.075> 2.011. From the data collected it can be concluded that the availability of raw materials and the production process both have a positive and significant effect on production results, which is indicated by the Fcount value exceeding the Ft. indicated by the Fcount value exceeding the Ftable value that has been determined which is 50.372> 3.20. If one of the variables is not fulfilled then result in the results of production not as expected by the company.